High productivity micro rotary swaging - Moumi Eric (MATEC Web of Conferences, 2018)
Rotary swaging is an incremental forming process with two main process variations plunge and infeed rotary swaging. With plunge rotary swaging, the diameter is reduced within a limited section whereas the infeed rotary swaging enables a diameter reduction over the entire workpiece length. The process is now subject to intensive investigation for manufacturing of micro parts. By increasing the process speed, failures occur particularly due to inappropriate material flow. In plunge rotary swaging, the workpiece material can flow radially into the gap between the dies and thus the workpiece quality suffers. In infeed rotary swaging the workpiece material flows against the feeding direction and can provoke bending or braking of the workpiece. Therefore, additional measures to control both the radial and the axial material flow to enable high productivity micro rotary swaging are investigated. The radial material flow during plunge rotary swaging can be controlled by elastic intermediate elements that enable an increase of productivity by factor three. A spring-loaded clamping device that enables an increase of the productivity by factor four can temporarily buffer the axial material flow in infeed rotary swaging against the feeding direction.